An Experience of School Evaluation in the Basque Country - Casado Goti, Martín; Zabaleta Ibáñez, Miren Nekane (Avances en Supervisión Educativa, 2023)
This paper is a description of some of the steps taken by the Education Inspection of the Basque Country in the evaluation of primary and secondary schools, taking into account the data obtained through their external and internal evaluations. The objetive is the best development of the students' competences.